Age structure of the workforce and firm performance - Christian Grund; Niels Christian Westergård-Nielsen (Institute for the Study of Labor (IZA), 2005)
In this contribution, we examine the interrelation between corporate age structures and firm performance. In particular, we address the issues, whether firms with young rather than older employees are successful and whether firms with homogeneous or heterogeneous workforces are doing well. Several theoretical approaches are discussed with respect to these questions and divergent hypotheses are derived. Using Danish linked employer-employee data, we find that both mean age and dispersion of age in firms are inversely u-shaped related to firm performance.
Keywords: M54; J21; L25; 330; firm performance; corporate age structures; demographic change; Arbeitskräfte; Altersgruppe; Unternehmensentwicklung; Schätzung; Dänemark